2021
DOI: 10.12688/f1000research.28393.1
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia and dysgeusia in SARS-CoV-2 infection: incidence and effects on COVID-19 severity and mortality, and the possible pathobiology mechanisms - a systematic review and meta-analysis

Abstract: Background: The present study aimed to determine the global prevalence of anosmia and dysgeusia in coronavirus disease 2019 (COVID-19) patients and to assess their association with severity and mortality of COVID-19. Moreover, this study aimed to discuss the possible pathobiological mechanisms of anosmia and dysgeusia in COVID-19. Methods: Available articles from PubMed, Scopus, Web of Science, and preprint databases (MedRxiv, BioRxiv, and Researchsquare) were searched on November 10th, 2020. Data on the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
2
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 282 publications
6
78
2
14
Order By: Relevance
“…Both of these symptoms were more common in COVID-19 compared to other respiratory infections (approximately 10 and 9 times, respectively). ( 13 )…”
Section: Discussionmentioning
confidence: 99%
“…Both of these symptoms were more common in COVID-19 compared to other respiratory infections (approximately 10 and 9 times, respectively). ( 13 )…”
Section: Discussionmentioning
confidence: 99%
“…Data extraction was conducted as explained in previous studies. 23 , 24 , 43 Briefly, important data from the eligible articles were extracted and whenever required supplementary materials were extracted. The list of references was retrieved to search for additional relevant studies.…”
Section: Methodsmentioning
confidence: 99%
“…The SARS-CoV-2 infection mainly affects the respiratory system, however, various other organs can also be affected 13 17 and with many unknown outcomes. Several studies have been conducted to assess the effects of SARS-CoV-2 on several affected health outcomes including those of the hepatic, 18 cardiovascular, 19 , 20 and central nervous systems, 21 , 22 and the occurrence of anosmia and dysgeusia, 23 as well as hemorrhagic and ischemic stroke. 24 Recently, gastrointestinal (GI) problems have emerged in patients with COVID-19, in particular diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 However, numerous other organs may also be impacted, 6 , 7 , 8 with numerous unknown consequences. 9 , 10 , 11 Furthermore, the COVID-19 Global cases database indicated that over 136 million confirmed COVID-19 cases had been reported as of April 12, 2021, resulting in 2,949,409 deaths. 12 The virus spreads quickly in through the world because of its high reproductive number R 0 , which is estimated to be 3.25 ≤ R0 ≤ 3.4, which means that one infected person can spread the virus to up to three unvaccinated people.…”
Section: Introductionmentioning
confidence: 99%